Insights into the spatio-temporal composition, diversity and function of bacterial communities in seawater from a typical laver farm - Liang, Zhourui; Jia, Rujie; Sun, Tengqin; Wang, Wenjun; Wang, Chao; Lu, Xiaoping (Frontiers in Marine Science, 2022)
Laver is the most widely farmed seaweed with the largest culture area in China. The spatio-temporal variations in composition, diversity, and functional properties of bacteria in seawater as well as the environmental variables of seawater in a large-scale laver farm in China were studied. Both the community richness indices and Shannon index in the laver farming area remained at a relatively stable level during laver cultivation. Fifty-nine prokaryotic phyla were detected in all samples, however, only six of these phyla accounted for 98.84% of all sequences. Proteobacteria, Gammaproteobacteria, Rhodobacterales, Rhodobacteraceae, and Octadecabacter were the most predominant bacterial taxa at different levels of classification. The keystone bacterial taxa were Bacteroidetes, Pseudomonadales, Rhodobacterales, Flavobacteriales, Loktanella, and Pseudoruegeria based on network analysis. Members of representative bacterial biomarker taxa in November may be associated with degradation of algal cell wall polysaccharides. A significant increase in metabolic exchange and transformation nutrients occurred in the seawater during the early and late stage of laver cultivation, indicating that the laver reproductive activities (i.e. the formation/release activities of archeospores and zygotospores) probably drove the variation of metabolic functional diversity of bacterial communities. Based on Mantel test and redundancy analysis, we found the hydrographic parameters (e.g. salinity, temperature, DO, pH) as well as the key carbon (e.g. POC, DOC) and nitrogen parameters (e.g. nitrate, DIN, DON, TDN) were crucial environmental variables to shape the bacterial community composition in the surrounding seawater of laver farm. In a word, our results suggested that the microbial community structure and function significantly changed across the different succession stages during laver cultivation. This work provides new insights on the characteristics of bacterial communities in a large-scale laver farming system and solidifies the importance of laver farming in shaping seawater microbiomes.